Video-assisted thoracoscopic surgery and mini-thoracotomy compared to conventional thoracotomy in the surgical management of pulmonary hydatid cyst - Al-Madhhachi, Bahaa Abdul Razzaq; Fahad, Ahmed Muhi; Ibrahim, Osamah Obaid (International Surgery Journal, 2022)
Background: Although hydatid cyst disease is not common in western countries, it is a public health issue in the Middle East, including Iraq. We describe a new method in the surgical management of the disease. Aim of the study was to evaluate the outcomes of different surgical approaches: video-assisted thoracoscopic surgery (VATS), mini-thoracotomy, and conventional thoracotomy in managing pulmonary hydatid cysts. Methods: Retrospective analysis of the surgical treatment of pulmonary hydatid cysts between January 2017 and December 2021 in two centers. Patients' data regarding the age, sex, sign and symptoms, cyst size and location, surgical approach, operative time, the intraoperative bleeding, chest drainage, hospitalization time, and postoperative complications. Results: A total of 122 patients were included in the study; 9 underwent VATS, 59 underwent mini-thoracotomy, and 54 had conventional thoracotomy. The VATS and mini-thoracotomy has superiority to the thoracotomy group in terms of lower duration of operation, less perioperative bleeding, early chest tube removal, and lower hospitalization time. Conclusions: VATS and mini-thoracotomy are safe and advantageous procedures compared to conventional thoracotomy.